A Portable Fluorescence Sensor with Improved Performance for Aniline Monitoring. Issue 34 (9th October 2022) - Gao, Xinxiang; Huang, Rongrong; Fang, Wan; Huang, Wei; Yin, Zihao; Liu, Yue; Huang, Xinyu; Ding, Liping; Peng, Haonan; Fang, Yu
Abstract: Aniline is an important biomarker in human exhaled breath for lung cancer, thus aniline sensing is of paramount importance. However, highly sensitive and selective detection of aniline in high moisture environment of exhaled breath is still challenging. In this work, a new fluorescence sensor for aniline with ultrahigh sensitivity is constructed. The o ‐carborane modified pyromellitic diimide derivative (CB‐PMI) is designed and prepared as the sensitive layer for the fluorescence sensor. As‐prepared sensing films exhibit a highly improved response toward aniline vapor. The good sensing performance of the fluorescence films in terms of response speed, selectivity, and reusability is also realized, and the detection limit can be as low as 0.1 ppt. The detection linear slope ranges from 1 to 50 ppt. In addition, a homemade portable sensing platform is successfully constructed, which may be a promising prototype for the future detection of modulating breath samples. The reported fluorescence sensor offers a new paradigm for the simple, low cost, and noninvasive diagnosis of lung cancer. Abstract : A new fluorescence sensor for breath aniline with ultrahigh sensitivity is constructed. As‐prepared sensing films exhibit a highly improved response toward aniline vapor, and the detection limit is lower than 0.1 ppt. In addition, a simple portable sensing prototype is successfully constructed for the future detection of modulating breath samples.